EKSISTENSI PRODUK MULTI LEVEL MARKETING DENGAN SKEMA PIRAMIDA DALAM SISTEM HUKUM DI INDONESIA - Arliyanda, Arliyanda (Tadulako Master Law Journal, 2020)
The problem of this research was criteria for MLM products with pyramid schemes and legal view in Indonesia for MLM products with pyramid schemes. This research was normative legal research that used primary and secondary legal material which then legal materials are analyzed qualitatively normatively by interpreting and constructing the statements contained in documents and legislation. The results of the discussion find out that good and healthy of MLM is in accordance with the Minister of Trade Regulation Republic of Indonesia Number: 13/M-Dag/Per/3/1006 concerning Provisions and Procedures for Issuance of Direct Selling Business Licenses and also fulfills the Good Corporate Governance principles, namely: Transparency, Accountability, Responsibility, Independency And Fairness. So, the criteria for MLM products with pyramid schemes are: first, products with low prices but not useful. Secondly, the product is expensive, but not qualified in accordance with regulations and does not meet the principles of Good Corporate Governance. While the legal view in Indonesia about MLM products with pyramid schemes is that this business is strictly against the law and prohibited in Indonesia, because business activities are not obtained from sales goods. However, by utilizing the opportunities for business partners to obtain rewards or income mainly from the costs of participating other people who join later and not from the sale of products, or from the sale of products, the products sold do not have quality that can be accounted for.